Concrete filled elliptical steel tubular members with large diameter-to-thickness ratio subjected to bending. (February 2016) - Uenaka, Kojiro; Tsunokake, Hisao
Abstract: Concrete filled elliptical steel tubes, hereafter called CFESTs, are elliptical steel tube members filled in with concrete. The CFEST belongs to a family of concrete filled steel tubes, the so-called CFT, having good deformability and large seismic strength due to confined effect between the tube and in-filled concrete. The present study aims to investigate experimentally the characteristics of the CFEST members under pure bending. The selected testing parameters are diameter-to-thickness ratio of elliptical steel tube and loading directions, namely, the minor and major axes directions. From the test results, both local buckling and cracking of the steel tube can be observed in compressive and tensile regions, respectively. Obtained pure bending strength of the CFEST is strongly affected by diameter-to-thickness ratio. Pure bending capacity of the CFEST is also compared to that of the circular CFT. Methods to predict pure bending strength of the CFEST based on concrete strength, yielding and fracture points of the steel tube and confinement effect are described. Moreover, pure bending strength of the CFEST members is mainly discussed in comparison to that of ordinary CFT members. Additionally, biaxial stress behavior of the steel tube induced by in-filled concrete is also mentioned.